Empowering Digital Innovation: The Impact Of Social Media Marketing on Brand Equity Mediated By Consumer Brand Engagement in The Local Perfume Sector Among Gen Z in Jakarta - Razzaq, Amadeo Yasir; Rabiah, Arbi Siti (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The emergence of local perfume brands in Indonesia corresponds with the heightened digital engagement of Generation Z, rendering social media an essential platform for cultivating brand equity and consumer loyalty. This study investigates the impact of Social Media Marketing (SMM) and Consumer Brand Engagement (CBE) on Brand Equity (BE) within the framework of local perfume consumption among Generation Z in Jakarta. Employing a quantitative research design and Partial Least Squares–Structural Equation Modeling (PLS-SEM) analysis with 270 participants, the results demonstrate that SMM exerts a significant positive influence on both CBE and BE. Moreover, CBE shows a substantial positive effect on BE, indicating that engaged consumers tend to develop stronger emotional and cognitive associations with local fragrance brands. The findings highlight that interactive, visually appealing, and personalized social media marketing content can enhance consumers’ emotional connection and behavioral involvement, thereby reinforcing brand equity. From a managerial perspective, this research underscores the need for local perfume brands to strengthen their digital marketing strategies through creative storytelling, influencer collaboration, and consistent brand messaging. Furthermore, the study emphasizes that sustainable improvements in SMM, CBE, and BE depend on the advancement of digital infrastructure and supportive government policies to enhance internet accessibility and technological adoption, aligning with Sustainable Development Goal 9 (SDG 9) Industry, Innovation, and Infrastructure. Overall, the study contributes to understanding the role of digital innovation in improving user experience and competitiveness within Indonesia’s fragrance industry.